The implementation of chaos-based PUF designs in field programmable gate array - Tuncer, Taner (Springer, 2016)
The security of cryptographic systems depends on the unpredictability, not being regenerate and good statistical properties of the random numbers. The numbers, generated to provide the peculiarities, need to be the true random ones. Another method for generating these numbers is physical unclonable functions based on ring oscillator (RO-PUF). PUFs show susceptibility to reverse engineering, emulation, man-in-the-middle and reconfiguration attacks. In this paper, the chaotic signs which were generated from logistic map are applied to the challenge of RO-PUF in order to prevent such undesirable occurrences. Chaotic-based RO-PUF was implemented on Altera's FPGA-based 60-nm EP4CE115F29C7 development boards by using VHDL language. The obtained random numbers passed the NIST statistical tests, accepted as standard for cryptographic applications. Additionally, the periodicity degree of the system is evaluated by the scale index method and correlations between the generated numbers are analyzed by the autocorrelation method to demonstrate their validity. The results of the developed system show that it is possible to prevent the attacks which PUFs are subjected to and increase the randomness of the obtained numbers as well.
Keywords: Logistic map; Ring oscillator; PUF; Statistical tests